2008
DOI: 10.1002/meet.2008.1450450279
|View full text |Cite
|
Sign up to set email alerts
|

The use of information sources by internet users in answering questions

Abstract: The purpose of this study was to investigate what kinds of sources people prefer to use when they answer questions online, especially, in the context of social Q&A. Social Q&A is a Web-based service, that allows people to ask questions and receive answers from their fellow users. In social Q&A, people often cite sources of information when they answer questions. It could be a name, a short description, or hyperlinks to the original sources. Yahoo! Answers was chosen for this study due to its popularity as a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 18 publications
(23 reference statements)
2
25
1
1
Order By: Relevance
“…However, there are a few contributions indicating the potential of Web 2.0 in this field. For example, Oh, Oh, and Shah (2008) demonstrated that community-based questioning and answering services allow people to ask questions and receive answers from their fellow users online. Interestingly, as the present study suggests, blogs may also be used for these purposes, though in a different way.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are a few contributions indicating the potential of Web 2.0 in this field. For example, Oh, Oh, and Shah (2008) demonstrated that community-based questioning and answering services allow people to ask questions and receive answers from their fellow users online. Interestingly, as the present study suggests, blogs may also be used for these purposes, though in a different way.…”
Section: Introductionmentioning
confidence: 99%
“…53 Although we do not know what percentage of reused answers are voted by the asker or by the social Q&A community as "best answers," it is reasonable to assume that some are. An evaluation of best Feature answer status is an explicit indication, especially if the evaluation is made by the asker, that a previously provided answer is relevant to answer a new question.…”
Section: Discussionmentioning
confidence: 99%
“…Answers responses. 21 A less recent but equally significant alternative form of question answering evolved from the information retrieval community. The Text Retrieval Conference (TREC) was instrumental in promoting the development of question-answering (QA) systems, by hosting a Question Answering Track for nine years, 1999-2007.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, at the source level, an initial list of core sources was compiled in order to guide a grounded assessment of sources accessed during the observational study. This was mainly based on three works (Hertzum & Pejtersen, 2000;Oh, et al, 2009;Peterson & Merino, 2003) and resulted in the following initial terms:…”
Section: Codingmentioning
confidence: 99%